2017
DOI: 10.1590/1983-21252017v30n409rc
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR IDENTIFICATION OF Liriomyza sp. IN THE NORTHEAST AND SOUTHEAST REGIONS OF BRAZIL

Abstract: -In Brazil, species of the genus Liriomyza are widely distributed and have economic importance as they cause damage to at least 14 plant families, especially Solanaceae, Cucurbitaceae, Asteraceae, and Fabaceae. Studies suggest existence of a species complex within this genus, based on the presence of morphological similarities among the species Liriomyza trifolii (Burgess), L. sativae Blanchard and L. huidobrensis (Blanchard). The present study aimed to use DNA barcoding to establish new distribution records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Thus, it generally requires dissection of the male genitalia for species identification, a difficult endeavour for non‐specialists. Regarding this, DNA barcoding plays an important and particularly useful subsidiary approach to help differentiate Liriomyza species (Ferreira et al, 2017; Kox et al, 2005; Nakamura et al, 2013; Scheffer, 2000; Scheffer et al, 2006; Scheffer & Lewis, 2005, 2006). Moreover, DNA barcoding facilitates identification of any life history stage of the specimen (e.g., larva, pupa, or adult).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it generally requires dissection of the male genitalia for species identification, a difficult endeavour for non‐specialists. Regarding this, DNA barcoding plays an important and particularly useful subsidiary approach to help differentiate Liriomyza species (Ferreira et al, 2017; Kox et al, 2005; Nakamura et al, 2013; Scheffer, 2000; Scheffer et al, 2006; Scheffer & Lewis, 2005, 2006). Moreover, DNA barcoding facilitates identification of any life history stage of the specimen (e.g., larva, pupa, or adult).…”
Section: Introductionmentioning
confidence: 99%
“…Leafminer flies of the genus Liriomyza (Diptera: Agromyzidae) are one of the main phytosanitary problems in melon (Cucumis melo L.) in the semi-arid region of Northeast Brazil (NUNES et al, 2013), with Liriomyza sativae Blanchard reported as predominant in cultivated areas (FERREIRA et al, 2017;CELIN et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The leafminer Liriomyza sativae (Blanchard, 1938) (Diptera: Agromyzidae) is an important pest in the melon crop (Cucumis melo L., 1753 ) in Brazil (Araujo et al, 2013;Ferreira et al, 2017). The larvae of this agromizid consume the leaf mesophyll, causing the reduction of the plant photosynthetic capacity and the total soluble solids content ( o Brix) of the fruit (Araujo et al, 2013;Costa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%